Hepatitis C virus infection in children and adolescents. (June 2019) - Indolfi, Giuseppe; Easterbrook, Philippa; Dusheiko, Geoffrey; El-Sayed, Manal H; Jonas, Maureen M; Thorne, Claire; Bulterys, Marc; Siberry, George; Walsh, Nick; Chang, Mei-Hwei; Meyers, Tammy; Giaquinto, Carlo; et al.
Summary: Hepatitis C virus (HCV) infection is a major cause of chronic liver disease and associated morbidity and mortality worldwide. Short-course, oral, curative, direct-acting antiviral regimens have transformed treatment for HCV infection. Since the 2016 launch of the first global strategy towards elimination of viral hepatitis as a public health threat by 2030, the predominant focus of the global response has been on the treatment of adults, who bear the greatest burden of morbidity and mortality of HCV-related chronic liver disease. Compared with adults, there has been little attention paid to addressing the response to HCV in children and adolescents, in part because of the scarcity of data to inform specific paediatric management practices and policy. In this Series paper, we summarise knowledge on the epidemiology, natural history, and treatment of chronic HCV infection in adolescents and children, and we highlight key differences from infection acquired in adulthood. The estimated global prevalence and burden of HCV infection in children aged 1–19 years is 0·15%, corresponding to 3·5 million people (95% CI 3·1–3·9 million). HCV infection is usually asymptomatic during childhood, and cirrhosis and hepatocellular carcinoma are rare. Sofosbuvir with ledipasvir and sofosbuvir with ribavirin have received regulatory approval and guidelines recommend their use in adolescents aged 12 years and older with HCV infection. In April, 2019, glecaprevir with pibrentasvir also received regulatory approval for adolescents aged 12–17 years. Key actions to address the current policy gaps and achieve treatment scale-up that is comparable to that in adults include: establishment of a campaign on access to testing and treatment that is targeted at children and adolescents; fast-track evaluation of pan-genotypic regimens; and accelerated approval of paediatric formulations. Research gaps that need to be addressed include: age-specific prevalence studies of HCV viraemia in priority countries; further validation of non-invasive tests for staging of liver disease in children; and establishment of paediatric treatment registries and international consortia to promote collaborative research agendas.